Effect of Rabbit Compost and NPK on The Growth and Yield of Zucchini (Cucurbita Pepo L.) - I Putu Tommy Saputra Adi; Made Sri Yuliartini; I Gusti Bagus Udayana (SEAS (Sustainable Environment Agricultural Science), 2020)
This study aims to determine the effect of the type of rabbit compost and the dose of NPK fertilizer on the growth and yield of zucchini plants. The design used in this study was a factorial randomized block design (RBD) consisting of 2 factors, namely: The first factor is rabbit compost (K) which consists of 4 levels of treatment, namely: K0 = 0 tonnes / ha, K1 = 10 tonnes / ha, K2 = 20 tonnes / ha, K3 = 30 tonnes / ha. The second factor, NPK pearl fertilizer dosage (D) consists of 4 levels, namely: D0 = 0 kg / ha-1, D1 = 100 kg / ha-1, D2 = 200 kg / ha-1, D3 = 300 kg / ha -1. Thus, there were 16 combination treatments, each of which was repeated 3 times so that there were 48 experimental plots. The research data were analyzed statistically using analysis of variance. For a single treatment that has a real to very real effect, it is followed by the BNT test at 5% level, the results showed that the interaction between rabbit compost dose and NPK (KxD) had no significant effect (Pâ‰¥0.05) on all variables. The highest fresh fruit weight was obtained at the rabbit compost dose of 30 tons / ha (K3), namely 2463.64 grams, an increase of 16.09% when compared to the treatment without compost dose of 0 tons / ha (K0), namely 2084.30 grams . The high fresh weight was supported by the number of harvests per plant (r = 0.821 *), fruit length (r = 0.935 **) and fruit diameter (r = -0.975 **). The highest fruit fresh weight was obtained at the NPK fertilizer dose of 300 kg / ha (D3), namely 2488.95 grams. The fresh weight of the fruit increased by 18.23% when compared to the NPK fertilizer dose of 0 ton / ha (D0), which was 2104.87 grams. The high fresh weight of fruit was supported by the number of harvests per plant (r = 0.923 **)